The Histone Deacetylase Inhibitory Potential of Chicken Egg Yolk Fat and Their Fatty Acid Composition - Meran Keshawa Ediriweera (Scientifica)
Histone deacetylation is a key biochemical event associated with transcriptional regulation. Histone deacetylases (HDACs) mediate the deacetylation of histones. Fatty acids have been reported to function as histone deacetylase inhibitors (HDACi). The present instigation reports the HDAC inhibitory activity of egg yolks and egg yolk-derived fat of country and farm chicken for the first time. Egg yolks and fatty acids derived from both country (CCEF) and farm chicken (FCEF) demonstrated significant HDAC enzyme activity inhibition. Furthermore, egg yolks, CCEF, and FCEF exhibited DPPH free radical scavenging effects. The analysis of fatty acid profiles revealed varying degrees of saturated, mono-, and polyunsaturated fatty acids in the egg yolks. Palmitic acid (C16 : 0) was found to be the most abundant saturated fatty acid in both CCEF and FCEF. Among the monounsaturated fatty acids, oleic acid (C18 : 1) was the most abundant in both CCEF and FCEF. In terms of polyunsaturated fatty acids, a significant difference was observed in the content of linoleic acid (C18 : 2), an omega-6 fatty acid, and docosahexaenoic acid (C22 : 6), an omega-3 fatty acid, between CCEF and FCEF. These findings present exciting prospects for the development of histone deacetylase inhibitors based on egg yolk fat.